ASIDOLISIS ENZIMATIS MINYAK SAWIT MERAH DAN MIINYAK IKAN TUNA DENGAN BIOKATALIS LIPASE PADI MENGHASILKAN ASAM LEMAK KAYA OMEGA -3 - Wahyuningsih Wahyuningsih; Margaretha Tuti Susanti; Moh Endy Yulianto (METANA, 2021)
Abstract   Red palm oil is source of p carotene and vitamin E, while Tuna fish is source of omega-3 and 6. Diversification of palm oil and tuna fish oil can be used as food supplement. The utilization of high concentration of minor vitamin is one of strategy to increase the additional value of both oil and also to provide minor vitamin from local product in order to increase the healthy of the society. There was some research conducted on micro encapsulation process of red palm oil which is rich of P carotene, provitamin A, and provitamin E. And there was also research subjected to microencapsulated fish oil which is rich of omega-3. In this research we combined the microencapsutaion of both red palm oil and tuna fish oil through enzymatic cytolysis process. From the cytolysis process, we will got type of fatty acid which is rich of omega 3 and P carotene . The objective of the research were to study the activity of rice bran lipase as biocatalisator in the conversion of palm oil fatty acid into fatty acid which is rich of omega-3, and to develop the bioreactor for the enzymatic cytolysis for fatty acid production. The research result showed that optimum condition for the cytolysis process was the ratio of red palm oil tuna fish oil 3:1, temperature 40oC; reaction time 4 hours, where the yield of fatty acid has EPA and DHA concentration 35,92% and 5,65%, respectively. While the rate of the reaction was 619,67 mol/hour. Red palm oil is an alternative source of fatty acid which is rich of omega 3 (EPA and DHA), and it can be produced by enzymatic cytolysis by using rice bran lipase. Lipase enzyme of R Meithei found to be a good biocatalyst in the red palm oil and tuna fish incorporation process of the fatty acid which is rich of omega-3.   Key words: citolysis, red palm oil, tuna fish oil